The Optimism and the Small Techno Theater: Re-life, Destined for the Future - Sungkawadee, Ratchakan (Journal of Cultural Approach, 2021)
This research aimed to 1) study the optimistic variables, the satisfaction in the drama’s success, and the happiness in work of the small techno theater team: re-life, destined for the future, and 2) study the correlation between the optimistic variables, the satisfaction in the drama’s success, and the happiness in work of the small techno theater team: re-life, destined for the future. The sample group used in the research was the audience, 250 people, by coincidental random sampling. The researcher used the optimistic theory, in the aspect of the audiences’ satisfaction as a research tool. The questionnaires had reliable values from .86 - .93. The statistical analysis was used for the data analysis by using the Hierarchical Stepwise Regression. The results of the research on important issues found that: The optimism in the teamwork could predict the results with the statistical significance at level .001. Additionally, the happiness in the work of the small techno theater team: Re-life, destined for the future, and the satisfaction in the drama’s success could also predict the results as well. The optimism and the satisfaction in the drama’s success could predict the success of the drama in a positive way with the statistical significance at level .001. The overall satisfaction of the audiences who had watched the small techno theater team: Re-life, destined for the future could predict that the direction of the optimism in the aspect of the happiness in work of the small techno theater team will be in a positive direction with the statistical significance at level .05.